The impact of educational attainment on labor market outcomes - Kalpana Pai (Luxembourg Income Study (LIS), 2008)
This paper studies the impact of educational attainment on Labor Market outcomes using data from the Luxembourg Income Study (LIS) for 10 countries over a multi-year period. The 10 countries in this study include USA, Mexico, Germany, Netherlands, Italy, Finland, Spain, Norway, Australia, and Taiwan. We use person level data from the LIS for this study. By including 10 countries in the analysis, we are able to examine the differences in labor market returns in these countries. We are also able to analyze the gender difference in wages across these countries for low, medium, and high levels of educational attainment.
Keywords: 330; Bildungspolitik; Bildungsniveau; Bildungsertrag; Lohnstruktur; OECD-Staaten